Legal Regulation of the Activities of the Bodies of the National Police of Ukraine on Ensuring the Exercise of the Right to Freedom of Peaceful Assembly - M. A. Sambor (Bulletin of Kharkiv National University of Internal Affairs)
Under the conditions set out in Part 2 of Art. 19 of the Constitution of Ukraine of the legal order in Ukraine, according to which state bodies to which the National Police of Ukraine belongs, their officials are obliged to act only on the basis, within the powers and in the manner provided by the Constitution and laws of Ukraine, is usually an important issue regulatory and legal regulation of the activities of the bodies of the National Police of Ukraine on ensuring the exercise of the right to freedom of peaceful assembly. The article examines the legal acts, namely the Law of Ukraine “On the National Police”, the Criminal Procedure Code of Ukraine, the Resolution of the Cabinet of Ministers of Ukraine, as well as the departmental regulatory acts of the Ministry of Internal Affairs of Ukraine, the Head of the National Police of Ukraine regarding the right to exercise the right to freedom of peaceful assembly.